Giant colonic diverticulum of the transverse colon as a rare cause of surgical acute abdomen: A case report (Indian Journal of Case Reports, 2024)
A colonic diverticulum larger than 4 cm in size is referred to as a giant colonic diverticulum and is an uncommon occurrence. Globally, <200 cases of large colonic diverticula have been documented. The majority of the giant colon diverticulum arises from the sigmoid colon. However, we here described a case report of a 68-year-old female who presented with acute abdominal pain, along with chronic constipation. An abdominal computed tomography scan revealed an enormous giant colonic diverticulum measuring 17 cm × 11.7 cm × 7.8 cm with a 1.3 cm neck orifice, arising from the transverse colon along the antimesenteric border of the colon. The patient underwent an exploratory laparotomy with excision of the transverse colonic giant diverticulum and stapler anastomosis.